MAFLD Criteria Guide the Subtyping of Patients with Fatty Liver Disease - Huang J; Ou W; Wang M; Singh M; Liu Y; Liu S; Wu Y; Zhu Y; Kumar R; Lin S (Risk Management and Healthcare Policy, 2021)
Jiaofeng Huang,1 Weijie Ou,1 Mingfang Wang,1 Medha Singh,2 Yuxiu Liu,1 Shiying Liu,1 Yinlian Wu,1 Yueyong Zhu,1,3 Rahul Kumar,4,* Su Lin1,* 1Department of Hepatology, Hepatology Research Institute, The First Affiliated Hospital, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 2Department of General Medicine, Tan Tock Seng Hospital, Singapore; 3Fujian Key Laboratory of Precison Medicine for Cancer, The First Affiliated Hospital, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 4Department of Gastroenterology and Hepatology, Duke-NUS Academic Medical Centre, Changi General Hospital, Singapore*These authors contributed equally to this workCorrespondence: Su LinDepartment of Hepatology, Hepatology Research Institute, The First Affiliated Hospital, Fujian Medical University, No. 20, Chazhong Road, Taijiang District, Fuzhou, Fujian, 350005, People’s Republic of ChinaEmail sumer5129@fjmu.edu.cnBackground and Aims: Metabolic associated fatty liver disease (MAFLD) is diagnosed in patients with hepatic steatosis when they have the following three metabolic conditions: obesity/overweight, diabetes and metabolic dysregulation, either alone or in combination. There is no clarity whether subtypes of MAFLD diagnosed by different metabolic conditions carry different levels of risk for intra- and extra-hepatic organs. This study aims to depict the characteristics of these subtypes in a large population.Methods: The data were retrieved from the third National Health and Nutrition Examination Surveys of the United States. The clinical and biochemical features in different MAFLD subtypes were compared. The outcome of interest was significant and advanced fibrosis.Results: Out of 4,087 (31.24%) participants with MAFLD, 1,165 (28.51%) were diagnosed by single metabolic condition, 2,053 (50.23%) by two conditions, and 869 (21.26%) by all three metabolic conditions. With increasing numbers of metabolic conditions, participants tended to be older, were more likely to be female, and had more severe renal impairment and liver fibrosis (P< 0.05). MAFLD patients with a lower number of metabolic conditions were more likely to have excessive alcohol consumption. Among MAFLD with single metabolic condition, those diagnosed by diabetes alone had the highest proportion of advanced fibrosis identified by non-invasive fibrosis models (P< 0.05).Conclusion: More metabolic conditions upon the diagnosis of MALFD indicate higher risk of fibrosis. Patients with MAFLD diagnosed by diabetes alone are more likely to have advanced hepatic fibrosis than those with other metabolic conditions alone. Individualized management is required for MAFLD with different subtypes.Keywords: metabolic associated fatty liver disease, nonalcoholic fatty liver disease, metabolic syndromes, NHANES, fibrosis